Lenz microphthalmic syndrome in an Indian patient - Gupta Arvind; Srinivasan Renuka; Pandian Datta; Babu K (Indian Journal of Ophthalmology, 2007)
A case of Lenz microphthalmia syndrome in a seven-month-old male child having features of unilateral anophthalmia, microcephaly, external ear and finger abnormalities, hydrocele and hypospadias is being reported. The unilateral involvement and anophthalmia is rare in Lenz syndrome. The manifestation of hydrocele in association with this syndrome has not been seen in earlier cases. This is the first documented case from India.